Organizing an international‐standard obstetric ultrasonography training program in a low‐resource setting. Issue 1 (3rd November 2016) - Enabudoso, Ehigha; Adams, Osikhueme H.
Abstract : A short, intensive training course in obstetric ultrasonography was organized in a low‐resource setting. Participant self‐assessment scores demonstrated the success of the course.